2016
DOI: 10.1002/chem.201602964
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Catalysis for Selective Alcohol Oxidation with Molecular Oxygen

Abstract: The activation of dioxygen for selective oxidation of organic molecules is a major catalytic challenge. Inspired by the activity of nitrogen-doped carbons in electrocatalytic oxygen reduction, we combined such a carbon with metal-oxide catalysts to yield cooperative catalysts. These simple materials boost the catalytic oxidation of several alcohols, using molecular oxygen at atmospheric pressure and low temperature (80 °C). Cobalt and copper oxide demonstrate the highest activities. The high activity and selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 43 publications
(89 reference statements)
4
47
0
Order By: Relevance
“…It is important to know the amount of functional groups present in support, their both decomposition and stability, because those groups can interact with the active phase Co 3 O 4 and with molecular oxygen. This promotes the generation of active oxygen species, superoxide, and peroxides mainly, which will interfere in the oxidation reaction of alcohols [14,34,35]. These analyses are consistent largely with the IR analysis and TPR-H 2 ( Table 1).…”
Section: Characterization Of the Supports And Catalystssupporting
confidence: 80%
“…It is important to know the amount of functional groups present in support, their both decomposition and stability, because those groups can interact with the active phase Co 3 O 4 and with molecular oxygen. This promotes the generation of active oxygen species, superoxide, and peroxides mainly, which will interfere in the oxidation reaction of alcohols [14,34,35]. These analyses are consistent largely with the IR analysis and TPR-H 2 ( Table 1).…”
Section: Characterization Of the Supports And Catalystssupporting
confidence: 80%
“…Interestingly, there is a marked difference between the oxidation of activated alcohols, which we reported earlier, and that of cyclohexene. With an activated alcohol substrate such as cinnamyl alcohol, the N:C support is required for oxygen activation.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we showed that this problem can be solved for the specific case of the oxidation of activated alcohols to aldehydes and ketones by using a bifunctional catalyst . Yet this oxidation was “only” a dehydrogenation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…As part of our ongoing research into selective oxidation with molecular oxygen, we tried building synthetic porphyrin analogues that could serve as good single‐atom catalysts in vitro . For this, we turned to phthalocyanines (Pcs), which are highly stable two‐dimensional macrocycles with a structure analogous to that of porphyrins (Scheme ).…”
Section: Introductionmentioning
confidence: 99%